Synthesis, biological activities and pharmacokinetic properties of new fluorinated derivatives of selective PDE4D inhibitors. Issue 13 (1st July 2015) - Brullo, Chiara; Massa, Matteo; Villa, Carla; Ricciarelli, Roberta; Rivera, Daniela; Pronzato, Maria Adelaide; Fedele, Ernesto; Barocelli, Elisabetta; Bertoni, Simona; Flammini, Lisa; Bruno, Olga
Graphical abstract: Abstract: A new series of selective PDE4D inhibitors has been designed and synthesized by replacing 3-methoxy group with 3-difluoromethoxy isoster moiety in our previously reported cathecolic structures. All compounds showed a good PDE4D3 inhibitory activity, most of them being inactive toward other PDE4 isoforms (PDE4A4, PDE4B2 and PDE4C2). Compound3b, chosen among the synthesized compounds as the most promising in terms of inhibitory activity, selectivity and safety, showed an improved pharmacokinetic profile compared to its non fluorinated analogue. Spontaneous locomotor activity, assessed in an open field apparatus, showed that, differently from rolipram and diazepam, selective PDE4D inhibitors, such as compounds3b, 5b and7b, did not affect locomotion, whereas compound1b showed a tendency to reduce the distance traveled and to prolong the immobility period, possibly due to a poor selectivity.